Contos de Grimm e novos contos de Grimm: tradução e adaptação em Monteiro Lobato - TRUSEN, Sylvia Maria (Universidade Federal do Pará, 2017)
Monteiro Lobato’s work is well known in the field of literature for children, and so is his effort to emancipate the genre of European canons. However, his task as translator to transfer and circulate a large number of foreign literature works within the national environment, seems to contradict his project of founding a own Brazilian children’s literature. With the review of the reception of the Grimm´s collection in his work, especially the adaptations of Grimm Fairy Tales and the New Tales of Grimm, the task is therefore to analyse how Lobato has reconciled the purposes in apparently disagree.